A theoretical and numerical study of an additional viscosity term in a modified elasto-plastic friction model for wet friction clutch simulations - Petrun, Tomaž (Strojniški vestnik, 2013)
This paper deals with a theoretical and numerical study of various viscosity terms in the modified elasto-plastic friction model and its influence on the resulting friction force-torque, transmitted through the contact of the friction clutch. Various simple viscous definitions for fluids considering shear rate dependent viscosity were investigated. As a basis for the research the Carreau fluid model was chosen, since it can describe Newtonian, dilatant and pseudo plastic fluids. Besides of theoretical investigations, numerical simulations at realistic friction clutch operation conditions were carried out. The results were compared to the results of a validation case for a dry friction clutch simulation with the modified elasto-plastic friction model. This research showed significant differences between various viscosity definitions and revealed the drawbacks of such a simplified approach. In addition to viscosity, a possibility to calculate the generated heat due to friction and its influence on the contact temperatures is discussed briefly. The basic theory and equations are given along with the directions for future work. The requirements for an accurate temperature calculation in the friction contact are outlined.
Keywords: Carreau fluid; Carreaujev fluidni model; dinamika sistema teles; elastoplastični modeli trenja; enostavni viskozni modeli; friction clutch simulation; friction model; simple viscosity models; torne sklopke